BAX In situ hybridization and proliferating cell nuclear antigen immunohistochemical expressions in salivary gland tumours - Qutaiba A Hussain; Lehadh M Al- Azzawi (College of Dentistry/ University of Baghdad, 2014)
Background: Epithelial salivary gland tumours are relatively uncommon and constitute a wide spectrum of variable morphologic and biologic entities. The cell proliferation / death balance is most important in the development of salivary gland tumours. The aim of this study was to examine the expression of PCNA protein immunohistochemically and Bax mRNA gene using in situ hybridization techniques and to correlate between the clinicopathological features of salivary gland tumours with the expressions of PCNA protein and Bax mRNA. Materials and Methods: Forty nine formalin fixed paraffin embedded tissue blocks of epithelial salivary gland tumours were used in this study. Haematoxylin and Eosin stain was used for reassessment of the histopathologic diagnosis. The cell proliferation activity was examined by proliferating cell nuclear antigen (PCNA) immunohistochemistry and proapoptotic cell death Bax mRNA gene was analysed by in situ hybridization techniques. Results: Immunohistochemical analysis show high expression of PCNA and was noted in 8 of 12 pleomorphic adenoma cases (66.67%), 15 of 19 adenoid cystic carcinoma cases (78.95 %), 6 of 7 mucoepidermoid carcinoma cases (85.71%), and 3 of 5 adenocarcinoma case (60 %). Significant difference was found between labeling index of benign and malignant salivary gland tumours, while no significant relationship was noted in labeling index between adenoid cystic carcinoma and mucoepidermoid carcinoma neither between mucoepidermoid carcinoma and adenocarcinoma. In situ hybridization detection show low expression of Bax and was noted in only 3 cases of pleomorphic adenoma cases (25%), 10 cases in adenoid cystic carcinoma cases (52.63 %), however, mucoepidermoid carcinoma showed high expression of these markers than other salivary gland tumours, whereas adenocarcinoma show equal number of cases expressed both PCNA protein and Bax mRNA. No significant relationship was demonstrated between the immunostaining PCNA or Bax and the morphological growth pattern or patient clinical profile. Positive significant correlation was found between PCNA and Bax mRNA in pleomorphic adenoma, adenoid cystic carcinoma, mucoepidermoid carcinoma and adenocarcinoma cases. Conclusion: The high proliferative rate could explain the natural course of these tumours and the decreased expression of bax in salivary gland tumours indicate that loss of bax expression might give the tumour cells a double growth advantage because uncontrolled proliferation is combined with reduce cell death rate. The interaction may trigger a multistep process which is able to promote and may play a role in salivary gland tumour genesis, possibly by inhibiting the apoptosis mediated by Bax.